EVALUASI PSIKOEDUKASI TERHADAP PENINGKATAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK: KAJIAN LITERATUR - Jauhar, Muhamad; Agustiani, widya; Wijayati, Sugih (Universitas Harapan Bangsa Purwokerto, 2020)
Chronic kidney disease is one of the health problems in the world. Chronic kidney disease as a complication of other chronic diseases such as hypertension. Management of chronic kidney disease in the final stages is done through hemodialysis therapy. The therapy is carried out throughout the patient's life. One impact that occurs if the problem is not handled properly is a decrease in quality of life. One non-pharmacological intervention to improve the quality of life is psychoeducation. The design of this study used a literature review from the journal database PubMed and Google Scholar obtained 10 research articles. Keywords used are psychoeducation and, Chronic Kidney Disease